Student Heterogenity and Achievement: A Study on Policies at Arabic Education Department of IAIN Lhokseumawe - Syukran Syukran (Arabic Education Program IAIN Pekalongan, 2019)
The aims of this study is investigating the policy of Arabic Education Department in responding the students’ heterogeneity to improve Arabic achievement. It is expected to be the solution for the problem of heterogeneity. To reveal the facts, the authors used interview, observation, questionnaire, and documentation. In analyzing the data, the authors used qualitative descriptive analysis method. The result of this study revealed that the Arabic Education Department of Tarbiyah and Teacher Training Faculty IAIN Lhokseumawe used teaching methods and objectives clearly to reach the successful and directed learning. But it was not enough, because all of the students did not come from the same background. Some of them came from MA, SMK, SMA and Pesantren. Certainly, those who came from Pesantren have higher Arabic achievement than those from other schools. The authors concluded that the policies can equalize and reduce differences in student achievement, though there were many obstacles and shortcomings in the implementation of the policy in language development